Financing Management Paradigm in Islamic Commercial Banks : A Theoretical and Practical Review - Abdillah Qadry Azizi; Mugiyati Mugiyati (Pusat Riset dan Inovasi Nasional, 2025)
The financing management paradigm in Islamic commercial banks is an important foundation in the Islamic financial system that emphasizes justice, transparency, and usefulness. This study aims to examine how this paradigm is applied in the practice of financing management in Islamic banks, as well as the challenges and innovations it faces. Using a qualitative approach through literature study, this study found that the sharia paradigm in financing not only avoids usury, but also encourages productive partnerships and strengthening the people's economy through sharia-compliant contract principles. Various forms of financing such as murabahah, musyarakah, and ijarah are implemented with a strict risk management approach. On the other hand, challenges arise such as limited public understanding of sharia contracts, weaknesses in the control of property rights in murabahah, and inconsistencies in practices with DSN-MUI fatwas. Financing innovations, such as sharia credit cards and blockchain-based digitalization, are important solutions, but still require regulatory support and increased sharia financial literacy. The results of this study indicate the importance of a balance between managerial efficiency and sharia compliance in the financing management paradigm of Islamic banks.